2024
DOI: 10.2147/opth.s442414
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Technical Failures in a Diabetic Retinopathy Screening Program

Ian Brennan,
Stephen Kelly,
Edel McBride
et al.

Abstract: Purpose Diabetic retinopathy (DR) is a preventable cause of blindness detectable through screening using retinal digital photography. The Irish National Diabetic Retina Screening (DRS) programme, Diabetic RetinaScreen, provides free screening services to patients with diabetes from aged 12 years and older. A technical failure (TF) occurs when digital retinal imaging is ungradable, resulting in delays in the diagnosis and treatment of sight-threatening disease. Despite their impact, the causes of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In this research, Ian Gerard Brennan et al found that the type and duration of diabetes, dilated pupil status, and the presence of a lens on the device used for screening were significantly related to technical failure (TF). 1 Therefore we recommend that try Multimodal Imaging Techniques and Potential Future Directions which uses several imaging methods to check the quantity of retinal thickness and precise mapping of retinal topography. This is useful in assessing retinal thickness in non-clinically significant macular edema and clinically significant macular edema.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations
“…In this research, Ian Gerard Brennan et al found that the type and duration of diabetes, dilated pupil status, and the presence of a lens on the device used for screening were significantly related to technical failure (TF). 1 Therefore we recommend that try Multimodal Imaging Techniques and Potential Future Directions which uses several imaging methods to check the quantity of retinal thickness and precise mapping of retinal topography. This is useful in assessing retinal thickness in non-clinically significant macular edema and clinically significant macular edema.…”
Section: Dear Editormentioning
confidence: 99%
“…In conclusion we agree that it is important to carry out comprehensive interventions aimed at reducing TF rates and increasing the effectiveness of Diabetic Retina Screening programs to determine the significant impact of patient factors, especially cataracts, on TF rates. 1 As additional information, it is important to know that retinal imaging is a key component in the diagnosis and management of DR patients and a multimodal imaging approach is key, as multiple imaging modalities including dye-based fluorescein and optical coherence tomography angiography can provide clinically important complementary information. 3 …”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations